Editorial Notes - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2022)
We are happy to publish the 16th volume of the Journal to our readers with a new section on Research Methodology. We hope our valued readers will benefit from the added section.